A study on diamond grinding wheels with regular grain distribution using additive manufacturing (AM) technology. (15th August 2016) - Yang, Zhibo; Zhang, Mingjun; Zhang, Zhen; Liu, Aiju; Yang, RuiYun; Liu, Shian
Abstract: In this paper, a metal bound diamond grinding wheel with a regular grain distribution was fabricated based on 3D printing technology, which provides a solution to the irregular grain distribution and complicated preparation processes of diamond grinding wheels for use in precise/ultraprecise grinding. A grinding wheel was designed in 3D with pro/E, and the data transformation to the stereo-lithography format was carried out. The fabrication of the diamond grinding wheel was achieved with Ni-Cr alloy and diamond by 3D printing and sintering layer by layer. Scanning Electron Microscopy (SEM), Energy Dispersive Spectrometry (EDS) and X-ray diffraction (XRD) were employed to characterize the grains and the micro-structures between the substrate and the Ni-Cr alloy in the diamond grinding wheel, suggesting the infiltration mechanism of Ni-Cr towards the diamond and steel substrate. Finally, the grinding performance was evaluated with an experiment. It was shown that the abrasion of the diamond grinding grains was normal, and no grains fell off the wheel. Graphical abstract: Highlights: Under 3D laser printing, the Ni-Cr alloy in the 3D laser printing process showed good soakage behavior to diamond particles. The Ni-Cr alloy in the 3D laser printing process showed good soakage behavior to the steel substrates. Cr3 C2 was formed on the interface of the diamond grains. The diamond particles and the steel substrate formed a tight bond, which met the requirements for heavy load grinding.